Soliloquies: A Movement-based Approach towards Beckett’s Waiting for Godot - Riana Diah Sitharesmi (IJCAS (International Journal of Creative and Arts Studies), 2016)
The research entitled “Soliloquies: a movement-based approach towards Beckett’s Waiting for Godot” examines my understanding of the play, which is manifested in the form of a dance piece along with a writing component. The conceptual foreground is drawn from the circumstantial analysis of a duality of human’s strategies confronting the difficult situation in their waits. “Waiting for Godot” (WfG), the biggest iconic of modern theatre, is the baseline to address the pragmatic understanding towards human condition and human self-reflection. The research aims to discover an alternative way bringing the abstract concept of human condition into a tacit understanding of the dance performance as well as the writing component. Both literary investigation and artistic-based research are processed simultaneously to discover the coherence, through which the creative process would find the equilibrium in both practical and academic. The observation of WfG’s dramatic tension leads the choreographic process in focusing kinesthetic exploration to represent ‘body and mind’. The idea is manifested through the dance performance entitled “Soliloquies”, which uses the presence of Balinese and Javanese elements as a starting point as well as the development of individual aesthetic experiences of the dancers. The results of the research generate distinctive movement vocabularies to convey its choreographic structure, while they also challenge an intercultural dialogue in the process of studio research. It draws the conclusion that such investigation could articulate the manifestation of movement-based approach towards Beckett’s WfG, that is the absurd of human condition. It also brings out a hermeneutic sphere in the art process, which works for me, as a female Indonesian dancer, to reconstruct identity within Indonesia contemporary state.